2011
DOI: 10.1021/mp100368d
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety Assessment of Human Mesenchymal Stem Cells Engineered by Hybrid Baculovirus Vectors

Abstract: Mesenchymal stem cells (MSCs) hold promise for cell therapy, and implantation of MSCs engineered with a baculovirus transiently expressing the growth factor can augment the bone repair. To prolong the baculovirus-mediated transgene expression, we developed hybrid baculovirus vectors exploiting the FLP/Frt-mediated recombination for circular episome formation. Transduction of human MSCs with the hybrid baculovirus vectors harboring the osteoinductive bmp2 gene substantially extended the BMP2 expression and impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 50 publications
1
35
0
1
Order By: Relevance
“…In contrast, no fluorescent spots were associated with the chromosome in the cells transduced with an egfp-bearing baculovirus deficient in the IR/DR elements and CMV-SB cassette. 20 Figure 2 thus collectively indicated that the transgene persistence stemmed from gene integration into the host chromosome, thanks to the SB-mediated transposition.…”
Section: Comparison Of Orip/ebna1 Aav Itr and Sb Systemsmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, no fluorescent spots were associated with the chromosome in the cells transduced with an egfp-bearing baculovirus deficient in the IR/DR elements and CMV-SB cassette. 20 Figure 2 thus collectively indicated that the transgene persistence stemmed from gene integration into the host chromosome, thanks to the SB-mediated transposition.…”
Section: Comparison Of Orip/ebna1 Aav Itr and Sb Systemsmentioning
confidence: 89%
“…28 The CMV-EGFP cassette was also PCR amplified from pEGFP-N1 (Clontech, Mountain View, CA, USA) and subcloned into the oriP/EBNA1-containing pRep4 (Invitrogen, Carlsbad, CA, USA). The cassette comprising CMV-EGFP and oriP/EBNA1 was then subcloned into pFastBacDpolhDp10, whose polyhedrin and p10 promoters were removed from pFastBac DUAL 20 to yield pBac-COE-CE. To generate pBac-ITR-CE, the egfp gene from pEGFP-N1 was PCR amplified and subcloned into pAAV-MCS (Stratagene, Santa Clara, CA, USA) in between the CMV-IE promoter and the polyadenylation signal (pA).…”
Section: Preparation Of Recombinant Baculovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…For proliferation assays, iPSCs cultured in 96-well plates were transduced and analyzed at 3 days posttransduction (dpt) using a bromodeoxyuridine (BrdU) cell proliferation assay kit (Millipore) as described previously (8). The apoptosis of iPSCs was quantified by two-dimensional flow cytometry, using an Annexin V-PE (phycoerythrin) Apoptosis Detection Kit I (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%